Expression of immune-regulatory molecules in circulating tumor cells derived from patients with head and neck squamous cell carcinoma. (February 2019) - Chikamatsu, Kazuaki; Tada, Hiroe; Takahashi, Hideyuki; Kuwabara-Yokobori, Yuki; Ishii, Hiroki; Ida, Shota; Shino, Masato
Highlights: Detection of circulating tumor cells in patients with head and neck cancer. Expression of immune-regulatory molecules in circulating tumor cells. Comparison of PD-L1 expression between tumor tissue and circulating tumor cells. Abstract: Objectives: Circulating tumor cells (CTCs) are cells that have shed from tumor tissue into the bloodstream, and the detection and characterization of CTCs in head and neck squamous cell carcinoma (HNSCC) still remain a challenge. Materials and methods: CTCs were isolated from 30 patients with HNSCC with recurrent and/or distant metastasis, via the depletion of CD45-positive cells with magnetic beads and the expression of multiple epithelial markers (CK19, EpCAM, EGFR, and c-Met) was analyzed by RT-qPCR with a low concentration of RNA from the CTC population. We next investigated the expression of the immune-regulatory molecules, PD-L1, PD-L2, and CD47, in CTC-positive patients and the PD-L1 expression in CTCs was compared with that in tumor tissues. Results: Twenty-four (80.0%) of the 30 patients were positive for at least one epithelial-related gene. Among the 24 CTC-positive patients, 19 (79.2%), 20 (83.3%), and 17 (70.8%) patients were positive for CD47, PD-L1, and PD-L2, respectively. Interestingly, the expression of these three immune-regulatory molecules was positively correlated to each other. As expected, PD-L1 expression in the tumor tissue did not correspond completely with that in the CTCs. Conclusion: Although clinical application and/or characterization of CTCs are still developing, our findings suggest that the CTCs are rapidly becoming a powerful tool in cancer treatments that involve the use of immune checkpoint inhibitors.